Registro civil y secularización. Comparación entre Ecuador y Francia - Joël Hautebert (Ius Humani. Jornal do direito, 2016)
The study of the creation of the Registry Office of people and of its linkages with the Church’s sacraments gets us right to the heart of legal, political and religious paramount issues. The comparison of recent French and Ecuadorian histories, two historically Catholic countries but from different continents, offers a relevant outlook for analyzing such general problems. The many comments of the bishop and lawyer Juan Larrea Holguin on the theme of relationships between the sacrament of marriage (and of Baptism) and civil obligations (civil status) can be largely applied to France. The accurate understanding of institutions still requires to refer to their history. The origin of Civil Registration unveils the purpose of secular states according to a logic of secularization, that is a logic of fight against the Church. Thereafter, we observe the maintenance of rules developed for Civil Registration but in new national and international political contexts, that changed Church’s diplomatic choices. The directions taken by these two countries splited up very recently. This study on Civil Registration gives us a picture of the issue related to Church freedom in these contemporary times which raise questions again about the links of Church with secular law.